# Ex 5.5, 7 - Chapter 5 Class 12 Continuity and Differentiability

Last updated at Jan. 3, 2020 by Teachoo

Last updated at Jan. 3, 2020 by Teachoo

Transcript

Ex 5.5, 7 Differentiate the functions in, γ(logβ‘γπ₯)γγ^π₯ + π₯^logβ‘π₯ Let π¦ = γ(logβ‘γπ₯)γγ^π₯+ π₯^logβ‘π₯ Let π’ = γ(logβ‘γπ₯)γγ^π₯ , π£ = π₯^logβ‘π₯ π¦ = π’+π£ Differentiating both sides π€.π.π‘.π₯. ππ¦/ππ₯ = (π (π’ + π£))/ππ₯ ππ¦/ππ₯ = ππ’/ππ₯ + ππ£/ππ₯ Calculating π π/π π π’ = γ(logβ‘γπ₯)γγ^π₯ Taking log both sides logβ‘π’ = log γ(logβ‘γπ₯)γγ^π₯ logβ‘π’ = π₯ . log (logβ‘γπ₯)γ Differentiating both sides π€.π.π‘.π₯. π(logβ‘π’ )/ππ’ . ππ’/ππ₯ = (π(π₯ . log (logβ‘γπ₯)γ ) )/ππ₯ 1/π’ (ππ’/ππ₯)" =" π(π₯)/ππ₯ . log (log" " π₯) + π(log (log" " π₯))/ππ₯ Γ π₯ Using product Rule As (π’π£)β = π’βπ£ + π£βπ’ 1/π’ (ππ’/ππ₯)" =" 1 . log (log" " π₯) + (1/(log" " π₯) .π(log" " π₯)/ππ₯) Γ π₯ 1/π’ (ππ’/ππ₯)" =" log (log" " π₯) + (1/(log" " π₯) . 1/π₯) Γ π₯ 1/π’ (ππ’/ππ₯)" =" log (log" " π₯) + 1/logβ‘π₯ Γ π₯/π₯ 1/π’ (ππ’/ππ₯)" =" log (log" " π₯) + 1/logβ‘π₯ ππ’/ππ₯ " =" π’ (log (log" " π₯)" + " 1/logβ‘π₯ ) ππ’/ππ₯ = (logβ‘π₯ )^π₯ (log (log" " π₯)" + " 1/logβ‘π₯ ) ππ’/ππ₯ = (logβ‘π₯ )^π₯ ((logβ‘γπ₯ . γlog γβ‘(logβ‘π₯ ) +γ 1)/logβ‘π₯ ) ππ’/ππ₯ = (logβ‘π₯ )^π₯/logβ‘π₯ (logβ‘γπ₯ . γlog γβ‘(logβ‘π₯ )+γ 1) ππ’/ππ₯ = (logβ‘π₯ )^(π₯ β1) (logβ‘γπ₯ . γlog γβ‘(logβ‘π₯ )+γ 1) Calculating π π/π π π£ = π₯^logβ‘π₯ Taking log both sides . logβ‘π£=logβ‘γ (π₯^logβ‘π₯ )γ logβ‘π£ = log π₯ . logβ‘π₯ logβ‘π£ = (logβ‘π₯ )^2 (As πππβ‘(π^π )=π . πππβ‘π) Differentiating both sides π€.π.π‘.π₯. π(logβ‘π£ )/ππ₯ = (π(logβ‘π₯ )^2)/ππ₯ π(logβ‘π£ )/ππ₯ . ππ£/ππ£ = (π(logβ‘π₯ )^2)/ππ₯ π(logβ‘π£ )/ππ£ . ππ£/ππ₯ = (π(logβ‘π₯ )^2)/ππ₯ 1/π£ . ππ£/ππ₯ = (π(logβ‘π₯ )^2)/ππ₯ 1/π£ . ππ£/ππ₯ = 2 logβ‘π₯ . π(logβ‘π₯ )/ππ₯ 1/π£ . ππ£/ππ₯ = 2 logβ‘π₯ . 1/π₯ ππ£/ππ₯ = π£ ((2 logβ‘π₯)/π₯) ππ£/ππ₯ = π₯^logβ‘π₯ ((2 logβ‘π₯)/π₯) ππ£/ππ₯ = π₯^logβ‘π₯ /π₯ (2 logβ‘π₯ ) ππ£/ππ₯ = π₯^(logβ‘π₯ β 1) . 2 logβ‘π₯ ππ£/ππ₯ = γ2π₯γ^(logβ‘π₯ β 1) . logβ‘π₯ Hence ππ¦/ππ₯ = ππ’/ππ₯ + ππ£/ππ₯ Putting value of ππ’/ππ₯ & ππ£/ππ₯ π π/π π = (π₯π¨π β‘π )^(π βπ) (π+π₯π¨π β‘π.π₯π¨π β‘(π₯π¨π β‘π ) ) + γππγ^(πππ π βπ). πππβ‘π

Ex 5.5

Ex 5.5, 1
Important

Ex 5.5, 2

Ex 5.5, 3 Important

Ex 5.5, 4

Ex 5.5, 5

Ex 5.5,6 Important

Ex 5.5, 7 Important You are here

Ex 5.5, 8

Ex 5.5, 9 Important

Ex 5.5, 10 Important

Ex 5.5, 11 Important

Ex 5.5, 12

Ex 5.5, 13

Ex 5.5, 14 Important

Ex 5.5, 15

Ex 5.5, 16 Important

Ex 5.5, 17 Important

Ex 5.5, 18

About the Author

Davneet Singh

Davneet Singh is a graduate from Indian Institute of Technology, Kanpur. He has been teaching from the past 9 years. He provides courses for Maths and Science at Teachoo.